LEGAL, INSTITUTIONAL AND FINANCIAL FORMS OF STATE AID FOR DISABLED STUDENTS - Niedziółka, Monika (Management and Administration Journal, 2024)
One of the greatest challenges of the modern state is to care for and ensure the good life of its citizens. Elderly people, people with disabilities require additional care. This means that the state is expected to take special actions in this regard, as these are often different needs and problems than in the case of non-disabled people. For many years, numerous initiatives have been observed in Poland to meet these requirements: starting with the creation of legal, administrative or organizational frameworks, and ending with the transfer of funds for their implementation. This last issue is not the subject of the given article. In difficult post-pandemic times, with war in the background and in the situation of an increasingly intense economic crisis, financial issues take on special importance. The aim of the article is to analyse the system the supports the financing of the needs of people with disabilities. Support institutions and the mechanisms of their functioning, as well as financial issues, were the subject to analyses. Particular attention is paid to the financial situation of students with disabilities in Poland. The analysis of the extensive support system for students with disabilities in relation to the low rate of this group of students among all students in Poland suggests that it is non-financial considerations that are the main limitation of the study process for young people with disabilities.